The Effect of Book Tax Differences and Company Size on Earnings Persistence - R Aisy, Lathifah Mahdiyah; Iqbal, Muhammad (Universitas Gorontalo, 2025)
This study aims to examine the effect of book tax differences and company size on profit persistence in food and beverage companies listed on the IDX in 2018-2022. This research is a type of quantitative research and uses secondary data. Determination of the sample using purposive sampling method technique with a total of 18 food and beverage companies as research samples. The research method uses multiple linear regression analysis using the IBM SPSS version 26 analysis tool. The results of this study conclude that book tax differences have a significant effect on earnings persistence and company size has no significant effect on earnings persistence.